Angelika Berlejung – Michèle Daviau – Jens Kamlah – Gunnar Lehmann (eds.), Encyclopedia of Material Culture in the Biblical World. A New Biblisches Reallexikon (Tübingen: Mohr Siebeck 2022) - Lemański, Janusz (Verbum Vitae, 2022)
Book Review: Angelika Berlejung – Michèle Daviau – Jens Kamlah – Gunnar Lehmann (eds.), Encyclopedia of Material Culture in the Biblical World. A New Biblisches Reallexikon (Tübingen: Mohr Siebeck 2022). Ss. 1231. 169,00 €. ISBN 978-3-16148966-2.